ANALISIS PERUBAHAN ANGGARAN APBD KOTA BUKITTINGGI TAHUN 2020 DALAM RANGKA PENANGGULANGAN COVID-19 DI KOTA BUKITTINGGI - Nabilla Nabilla; Roni Ekha Putera; Hendri Koeswara (Jurnal Pemerintahan dan Kebijakan (JPK), 2022)
This study aims to analyze how the implementation of changes to the Regional Revenue and Expenditure Budget (APBD) of Bukittinggi City in the 2020 Fiscal Year that must be carried out in an effort to overcome Coronavirus Disease 2019 (Covid-19) in Bukittinggi City. This change was implemented based on central government guidelines including Government Regulation in Lieu of Law No. 1 of 2020 and Joint Decree of the Minister of Home Affairs and Minister of Finance No. 119/2813/SJ and 177/KMK.07/2020. This study uses a descriptive qualitative research method with the theory of the Budget Cycle. The results showed that the Bukittinggi City Government during the 2020 Fiscal Year had made seven budget changes with two of them being budget refocusing, this budget change was made based on the three main focuses of Covid-19, namely the fields of Health, Economy and Social Safety Nets which rely on The seven main local government organizations of Bukittinggi are the Health Service, Agriculture Service, Fire Service, Regional Disaster Management Agency, Public Works and Public Housing Service, Social Service, and the Environment Service. During the focus of this Covid-19 response activity, it has an impact on changes in the total city government budget which has decreased in the budget with a percentage change in Total City Revenue up to 14.08%, Total Expenditure decreased by 11.28%, but for Expenditures in the Unexpected Expenditure section ( BTT) has increased to a percentage of 2,119.48%.